A Place-Based Approach to Urban Policy: Reflections from the Prodamas Program in Kediri, Indonesia - Tauran, T.; Latip, Abdul Rahman Abdul (The Journal of Society and Media, 2025)
In the context of rising urban inequality, this article explores the potential of place-based approaches to urban development, using the Prodamas program in Kediri, Indonesia, as a case study. Prodamas is a city-funded initiative that allocates direct funding to neighborhood units (RT) to enable communities to plan and implement development projects tailored to their specific socio-spatial contexts. This study analyzes policy documents and empirical research on Prodamas, illustrating how it applies place-based principles within a decentralized governance framework in the Global South. It offers insights into how this hyperlocal policy mechanism operates effectively, emphasizing the roles of participatory mechanisms, administrative coordination, and institutional adaptation. Prodamas helps people get involved in their community, encourages cooperation between different sectors, and supports local ideas for urban development. This empowers the community in shaping their urban environment. However, it faces governance challenges like limited community capacity, regulatory rigidity, and political vulnerability.. This paper argues that long-term and scalable place-based initiatives require financial commitment and an institutional ecosystem that fosters adaptive learning and power sharing. It deepens the theoretical and practical discourse on how place-based strategies can advance effective and equitable urban governance in complex and decentralized situations.